PENGEMBANGAN LKPD BERBASIS PROYEK DALAM PEMBUATAN GEL HAND SANITIZER DAUN KESUM PADA MATERI BIOTEKNOLOGI SISWA XII TAMAN MULIA - Hani Sri Wahyuni; Mahwar Qurbaniah; Ari Sunandar; Agistha Wulandari (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
biology teachers at Taman Mulia Kubu Raya School, project-based student worksheets (LKPD) in making hand sanitizer gels and teachers also did not have experience in making kesum leaf hand sanitizer gels. This study aims to develop a project-based LKPD manufacture of kesum leaf hand sanitizer gel on biotechnology materials. Research is the development of Thiagrajan with amodified 4D model into 3D. student worksheets (LKPD) manufacture of hand sanitizer gels that are developed are feasible based on percentage of eligibility for media, material, and language experts are 92.87%, 84.88%, and 83.33%, respectively, with very decent criteria, can be used but need a little revision. The percentage of the questionnaire responses to the initial scale test and the large scale test were 89.99% and 92.70%, respectively, with very good the learning process. the results obtained, it shows that the student worksheets (LKPD) for students biotechnology materials.Kata kunci: Daun kesum, Hand Sanitizer, LKPD.